'Don't Even Get Us Started on Social Workers': Domestic Violence, Social Work and Trust—An Anecdote from Research. (10th November 2017) - Robbins, Rachel; Cook, Kate
Abstract: This paper explores the concept of trust in relation to social work, child protection and work on domestic abuse. Trust is a complex notion. Borrowing from the arguments of Behnia that trust is the outcome of a process, the paper uses the talk of women who have experienced social work in the context of domestic abuse and child protection to consider the barriers to trust building. The evidence is gathered from three focus groups which formed part of an evaluation of a 'Freedom Programme'. The findings highlight issues with trust building that start with the context of living with abuse and work outwards to considerations of professional power, social work systems and wider inequality, suggesting an ecological approach to the trust-building process. The key argument is that social workers will struggle to gain trust within a system that sees domestic abuse as a hurdle that mothers must overcome, rather than a trauma through which they should be supported. The experiences of the women in this research, however, do show that trust and respect for voluntary service are achievable and that practice which builds alliances with the voluntary sector and service users could develop more trusting relationships.